Cross-Linked Alginate Dialdehyde/Chitosan Hydrogel Encompassing Curcumin-Loaded Bilosomes for Enhanced Wound Healing Activity - Sarah A. Sideek; Hala B. El-Nassan; Ahmed R. Fares; Nermeen A. Elkasabgy; Aliaa N. ElMeshad (MDPI AG, 2024)
The current study aimed to fabricate curcumin-loaded bilosomal hydrogel for topical wound healing purposes, hence alleviating the poor aqueous solubility and low oral bioavailability of curcumin. Bilosomes were fabricated via the thin film hydration technique using cholesterol, Span® 60, and two different types of bile salts (sodium deoxycholate or sodium cholate). Bilosomes were verified for their particle size (PS), polydispersity index (PDI), zeta potential (ZP), entrapment efficiency (EE%), and in vitro drug release besides their morphological features. The optimum formulation was composed of cholesterol/Span® 60 (molar ratio 1:10 w/w) and 5 mg of sodium deoxycholate. This optimum formulation was composed of a PS of 246.25 ± 11.85 nm, PDI of 0.339 ± 0.030, ZP of −36.75 ± 0.14 mv, EE% of 93.32% ± 0.40, and the highest percent of drug released over three days (96.23% ± 0.02). The optimum bilosomal formulation was loaded into alginate dialdehyde/chitosan hydrogel cross-linked with calcium chloride. The loaded hydrogel was tested for its water uptake capacity, in vitro drug release, and in vivo studies on male Albino rats. The results showed that the loaded hydrogel possessed a high-water uptake percent at the four-week time point (729.50% ± 43.13) before it started to disintegrate gradually; in addition, it showed sustained drug release for five days (≈100%). In vivo animal testing and histopathological studies supported the superiority of the curcumin-loaded bilosomal hydrogel in wound healing compared to the curcumin dispersion and plain hydrogel, where there was a complete wound closure attained after the three-week period with a proper healing mechanism. Finally, it was concluded that curcumin-loaded bilosomal hydrogel offered a robust, efficient, and user-friendly dosage form for wound healing.